Pertanggung jawaban Hukum Platform Media Sosial terhadap Penyebaran Konten Deepfake Berbasis Artificial Intelligence dalam Kasus Penipuan Berkedok Ritual Uang Gaib Ujang Busthomi - Wilma Silalahi; Fitri Natasha Dachi (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of Artificial Intelligence (AI) technology has created various digital innovations, but it has also generated new forms of crime through the misuse of deepfake technology. This study aims to analyze the legal liability of social media platforms for the dissemination of AI-based deepfake content and the forms of legal protection for victims of digital fraud, particularly elderly groups, in the case of the “magical money ritual” scam using the identity of Ujang Busthomi. This research employs normative legal research methods using statutory and case approaches. The results show that perpetrators of deepfake fraud can be held criminally liable under Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the Electronic Information and Transactions Law and Article 378 of the Indonesian Criminal Code concerning fraud. In addition, social media platforms as Electronic System Providers also bear preventive and repressive responsibilities under the ITE Law, Government Regulation on Electronic Systems and Transactions, and the Personal Data Protection Law to prevent the spread of illegal content. Legal protection for victims is carried out through criminal law enforcement, personal data protection, restitution mechanisms, and the enhancement of digital literacy in society.